DEPENDENCE FUNDUS LESIONS ON THE TYPE OF DIABETES MELITUS - Bezkorovainaya, I.N.; Voskresenskaya, L.K.; Ryadnova, V.V.; Dobrianskaya, V.A. (World of Medicine and Biology, 2014)
The aim of our work was to study characteristics changes the fundus of the eye in various types of diabetes. An analysis of 34 patients who investigated the incidence of various types of ophthalmic complications of diabetes. It has been established that the thickness of the retina of patients with diabetes mellitus type 2 is greater than in patients with diabetes type 1. Patients with type 1 diabetes, diabetic retinopathy are a most progressive and have more complications. It is necessary to perform periodic optical coherence tomography for the observation and comparison the state of the fundus and development the ophthalmic complications.
Keywords: diabetes; diabetic retinopathy; optical coherence tomography